Pedagogical Virtues: An Account of the Intellectual Virtues of a Teacher - Clemente, Noel L (Archīum Ateneo, 2022)
The overlap between virtue epistemology and the philosophy of education has been dominated by discussions of the epistemic qualities of good learners, that is, the intellectual virtues that must be nurtured in students. Not much has been said about the epistemic qualities of good teachers expressed in virtue-theoretic terms. This paper offers a preliminary account of such qualities, which are designated as pedagogical virtues. I use Battaly's pluralist conception of intellectual virtue as a starting point, then describe a pedagogical virtue as an intellectual virtue with an other-regarding success or motivational component. I end with an elucidation of the pedagogical versions of two mainstream intellectual virtues, perseverance and inquisitiveness.